ANALISIS FAKTOR PENYEBAB RENDAHNYA KEMAMPUAN MEMBACA SISWA KELAS III SDN 2 BUMI NABUNG UTARA - Wulandari, Vera; Aris, Ika Evitasari; Rahayu, Maulina (Jurnal Inovasi dan Teknologi Pendidikan, 2025)
This study aims to analyze the factors contributing to the low reading ability of third-grade students at SDN 2 Bumi Nabung Utara. The research is based on the importance of reading skills as a fundamental foundation for students’ academic success in elementary school. Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation to capture the real conditions in the field. The findings reveal two main influencing factors: internal and external. Internal factors include low intelligence, lack of learning motivation, and limited reading interest. External factors consist of conventional teaching methods, insufficient parental support, limited learning facilities, and an unconducive learning environment. These factors interact and directly affect students’ literacy development. Therefore, improving reading skills requires collaboration among teachers, parents, and schools through innovative teaching methods, intensive guidance, and the provision of adequate reading facilities.